Artemis fowl : the Arctic incident / 2. - Colfer, Eoin (Artemis Fowl, 2002)
Artemis is at boarding school in Ireland when he receives an urgent video e-mail from Russia. In it is a plea from a man who has been kidnapped by the Russian Mafiya -- a man Artemis had thought he would never see again: his beloved father. As Artemis rushes to his rescue, he is stopped by a familiar nemesis, Captain Holly Short of the LEPrecon fairy police. But this time, instead of battling the fairies, he is going to have to join forces with them if he wants to save one of the few people in the world he loves.